ENHANCING REPEAT PURCHASE INTENTION (ZALORA INDONESIA ON GEN Y) THROUGH E-SERVICE QUALITY, ETRUST, AND MODERATING ROLE OF PRIOR ONLINE EXPERIENCE - Mariana, Rika; Taufik, Taufik; Lutfi, Lutfi (Ridwan Institute, 2024)
E-commerce has emerged as one of the most developed sectors in the nation's digital economy, consisting of many transactions conducted over the internet, referred to as online sales and purchases. The fundamental success of an e-commerce comes from the results of the sales transactions carried out by consumers, therefore it is essential to convert prospective consumers into buyers who are motivated to conduct repeat purchases, which is the key to achievement in purchasing online, ensuring all businesses carries out various strategies by providing excellent service quality to create satisfaction and keep consumers loyal consequently to encourage repeat purchases. This research contributes to the understanding of how the factors or factors influence consumer behavior, specifically in the context of repeat purchase intention on ecommerce platforms like Zalora Indonesia. The study uses SEM-PLS (SmartPLS 3.0 software) and carried out through three stages, Outer model, Inner model, and hypothesis which inclusive direct and indirect effects. The measurement results show that the variables or factors generate positive and significant hypotheses about repeat purchase intentions, with the exception of the prior online experience variable, which produces negative results concerning the correlation between e service quality and repeat purchase intent, as evidenced by the classification of moderators, which serves as a predictor variable (Predictor Moderation). The study provides managerial implications for the city of Cilegon (particularly among Gen Millennials) to increase Repeat Purchase Intention in order to compete more effectively, especially against Shopee and Tokopedia.